2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1136.r3
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral arthroplasty for native knee fractures

Abstract: Aims The aim of this study was to investigate the rate of revision for distal femoral arthroplasty (DFA) performed as a primary procedure for native knee fractures using data from the Australian Orthopaedic Association National Joint Arthroplasty Registry (AOANJRR). Methods Data from the AOANJRR were obtained for DFA performed as primary procedures for native knee fractures from 1 September 1999 to 31 December 2020. Pathological fractures and revision for failed internal fixation were excluded. The five prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…5 In contrast, infection rates of up to 10% have been reported following the use of femoral endoprostheses for fracture. 26 One-year mortality rates have been favourable, at 16% for periprosthetic fractures around the hip and 13% for those around the knee. 4,5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In contrast, infection rates of up to 10% have been reported following the use of femoral endoprostheses for fracture. 26 One-year mortality rates have been favourable, at 16% for periprosthetic fractures around the hip and 13% for those around the knee. 4,5…”
Section: Discussionmentioning
confidence: 99%
“…5 In contrast, infection rates of up to 10% have been reported following the use of femoral endoprostheses for fracture. 26 One-year mortality rates have been favourable, at 16% for periprosthetic fractures around the hip and 13% for those around the knee. 4,5 In summary, these approaches can be used to expose the full length of the femur for the management of periprosthetic and interprosthetic fractures with plate fixation or revision arthroplasty.…”
Section: Cranial Cranialmentioning
confidence: 99%
“…In the studies included by Rubinger et al [ 14 ] reoperation rates ranged from 0 to 45%. Recent analysis from the AOANJRR reported revision rates of 12% for DFR in PDFF after 6 years [ 16 ] and 12% after 4 years in native knee fractures [ 17 ]. As in the AOANJRR, this study showed no significant difference between cemented and cementless stem fixation which might be caused by the low number of cementless DFR.…”
Section: Discussionmentioning
confidence: 99%
“…All four meta-analyses acknowledged the limited data, a high risk of bias and recommended further studies. Recently, two analyses from the Australian Joint Replacement Registry (AOANJRR) reported about DFR in PDFF [ 16 ] and native knee fractures [ 17 ]. Despite being one of the oldest Arthroplasty registry, the number of cases for analysis was limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is always reassuring to read reflections from those heavily involved in the analysis of registry data about its advantages, disadvantages, value moving forward, and in particular, how it could be improved. [8][9][10][11][12][13][14][15][16][17][18][19][20] We also broach optimal management in acute trauma with an excellent annotation from Vallier, 21 which will hopefully give insight and stimulate debate.…”
Section: Years Youngmentioning
confidence: 99%